A poverty line contingent on reference groups: Implications for the extent of poverty in some Asian countries - Satya R. Chakravarty; Nachiketa Chattopadhyay; Jacques Silber (Asian Development Bank Institute (ADBI), 2016)
This paper estimates the number of poor in various countries in Asia by applying an "amalgam poverty line", which is a weighted average of an absolute poverty line (such as 1.25 per day or 1.45 per day) and a reference income (such as the mean or the median income). The number of poor is computed under various values of the weight applied to the absolute poverty line, namely 100%, 90%, 66%, and 50%. The paper provides estimates of the headcount ratio and poverty gap ratio under the various scenarios for 25 different countries or regions examined.
Keywords: D31; D63; I32; O53; 330; Poverty; poverty line; poverty measurement; poverty headcount ratio; poverty gap ratio